Pengaruh Harga dan Diskon Terhadap Keputusan Pembelian Konsumen Pada Bolly Dept Store Sila Bolo - Puji Lestari; Muhajirin Muhajirin; Ismunandar Ismunandar (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to analyze the influence of prices and discounts on consumer purchase decisions at Bolly Dept Store Sila Bolo. Using quantitative methods, data was collected through a questionnaire distributed to 150 respondents who were customers of Bolly Dept Store. Multiple linear regression analysis was used to test the proposed hypothesis. The results of the study show that both price and discounts have a significant influence on consumer purchase decisions. Specifically, competitive prices and attractive discounts can significantly improve consumer purchasing decisions. This finding has implications for Bolly Dept Store management in designing pricing and discount strategies to increase sales and customer satisfaction.